The sword, famine and pestilence: Expectation of health and prosperity in the prophets - Williams, D. T. (Old Testament essays, 1988)
'The prophets' approach to a hollatlc salvation, embracing man's health, prsperity and political situation, is examined with particular reference to modem prosperity teaching and liberation theology. The prophets do proclaim a holistic and this-wordly judgment and salvation, but whereas they anticipate an imminent judgment, salvation is only to be received after an intervention by God.,